Applications and Challenges of Artificial Intelligence in Early Diagnosis and Precise Treatment of Lung Cancer - Shouyu ZHANG; Bojiang CHEN; Weimin LI (Zhongliu Fangzhi Yanjiu)
The incidence and mortality of lung cancer are extremely high, and the 5-year survival rate of patients after diagnosis is less than 20%; as such, early screening and intervention are important. However, doctors are overwhelmed with a large workload of CT scan review in a short period of time and should ensure that the rate of missed diagnosis and misdiagnosis is low. Artificial intelligence can assist doctors in early diagnosis and precise treatment of lung cancer, but this technology has problems. This paper reviews the application of artificial intelligence in the prediction of benign and malignant lung nodules, pathology, gene mutation, intervention scheme, treatment response, and prognosis and presents the corresponding challenges.